The motives for instagram usage and the topics of interest among students In Universiti Tunku Abdul Rahman - Lee, Kah Seng (2023)
Instagram is a combination of the words "instant camera" and "telegram." This social media platform allows the users to share photos and videos. In this era, instagram can be said as one of the most popular social media platforms among the people who age between 18-24 years old. The theoretical framework that I applied to study this topic is uses and gratification theory. The objectives of this research topic is to investigate the motives of university students are using Instagram among the students in Univerisiti Tunku Abdul Rahman and to investigate whether the role of gender and course of studies affecting a student's topic of interest on Instagram among the students in Univerisiti Tunku Abdul Rahman. For this research study, a quantitative research will be conducted by distributing an online survey which consists of 31 questions toward 75 students from Universiti Tunku Abdul Rahman Sungai Long campus. The finding shows that out of the 5 main aspects of motives for instagram usage, there are a total four main aspects which are including social interaction, documentation, escapism, and aspect of creativity are becoming the motives of Instagram usage for students in Univerisiti Tunku Abdul Rahman .Female students are more likely to look into topics of interest that are related to animals, celebrities' fashion, food, and lifestyle, according to the findings from the previous chapter, while male students are more likely to look into topics related to electronics & gadgets, foods, lifestyle, and possibly some memes. Moving on to the course of study, the research reveals that the majority of students who enrol in creative courses tend to select interests that are connected to their studies, such as those that revolve around animals, celebrities, clothing, food, lifestyle, and photography.